Heritage of the Past: Addressing Philippines Ecological Footprint and Local Wisdom Through Copra-Making Practice - Avila, Roel V (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2020)
This article emerged from the author’s apprehension regarding the lack of social sensitivity caused by the failure to connect the environment to the school lessons. Furthermore, creating balance and harmony within society and environment seemed impossible to realize in this sense. As in the Philippines in this case, schools often negated the significance to connect the environment to schools. From author point of view, the fact that the Philippines has strong ecological footprints and the local wisdom which can be traced through copra-making industry should not be discharged. The author examined this ecological intelligence which manifested inherently among the kinfolk of copra-makers by elaborating the indigenous cultural practices of the rural folks in the Philippines and making sense of those practices with metaphorization to advocate and conduct more connection in the classroom. As a result the highlighted indigenous processes that provided as a model in contextualizing sociological, cultural, and historical accounts as an ethno-pedagogical strategy of integrating nationalism in social sciences teaching.